Reliable measurements of physiologic ankle syndesmosis widening using dynamic 3D ultrasonography: a preliminary study - Seung Woo Cha (Ultrasonography, 2019)
Purpose The purpose of this study was to present a technique for measuring physiologic distal tibiofibular syndesmosis widening using 3-dimensional ultrasonography (3D-US) with an evaluation of its reliability, and to determine whether there were differences in the measurements between different dynamic stress tests. Methods We retrospectively evaluated 3D-US of 20 subjects with normal ankle syndesmosis. 3D-US was performed in neutral (N), dorsiflexion with external rotation (DFER), and weight-bearing standing (WB) positions at the anterior inferior tibiofibular ligament level in both ankles for comparison. Using 3D-US volume data, axial images were reconstructed at the level of the lateral prominence of the anterior tibial tubercle to ensure consistent measurements of the tibiofibular clear space (TFCS) by two radiologists. Results There was a wide range of TFCS values among the subjects (N, 1.2 to 4.2 mm; DFER, 2.3 to 4.8 mm; WB, 1.7 to 4.6 mm). When both ankles of each subject were evaluated, the side-to-side differences were less than 1 mm in all positions, with high intraclass correlation coefficient (ICC) values between both ankles (ICC, 0.85 to 0.93). The inter-rater agreement for all TFCS measurements between the two radiologists was excellent (ICC, 0.81 to 0.96). In comparisons between the two dynamic stress tests, the TFCS was significantly wider in the DFER position than in the WB position (DFER vs. WB, 3.3 mm vs. 2.9 mm; P<0.001). Conclusion Using 3D-US, we were able to consistently evaluate the TFCS with good reliability. In a comparison of the two dynamic tests, there was more significant widening of the TFCS in the DFER position than in the WB position.